The Role Of Gamification And Customer Loyalty Program On Customer Retention With E-Customer Satisfaction As An Intervening Variable - Ahmad Fikri; Supriadi Thalib; Agustinus Miranda (Universitas Pakuan, 2026)
The rapid growth of e-commerce in Indonesia has intensified competition among digital platforms, making customer retention a major challenge. This study aims to analyze the effects of gamification and customer loyalty programs on customer retention, with e-customer satisfaction as an intervening variable among Shopee e-commerce users. A quantitative approach was employed using a survey method with 240 respondents selected through purposive sampling. Data were collected via online questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (SEM-PLS). The results indicate that gamification and customer loyalty programs have a positive and significant effect on e-customer satisfaction and customer retention. Furthermore, e-customer satisfaction mediates the influence of gamification and customer loyalty programs on customer retention. These findings highlight the crucial role of customer satisfaction in strengthening long-term relationships between consumers and e-commerce platforms. This study contributes to the digital marketing literature and provides practical implications for e-commerce managers in designing marketing strategies that focus on enhancing customer satisfaction and retention.